2012
DOI: 10.1111/j.1742-4658.2012.08508.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of oscillatory phenotypes in Saccharomyces cerevisiae reveal a network of genome‐wide transcriptional oscillators

Abstract: Genetic and environmental factors are well-studied influences on phenotype; however, time is a variable that is rarely considered when studying changes in cellular phenotype. Time-resolved microarray data revealed genome-wide transcriptional oscillation in a yeast continuous culture system with ~2 and ~4 h periods. We mapped the global patterns of transcriptional oscillations into a 3D map to represent different cellular phenotypes of redox cycles. This map shows the dynamic nature of gene expression in that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 43 publications
(88 reference statements)
4
48
0
Order By: Relevance
“…Fermentor culture conditions for CEN.PK113-7D oscillating with a 4 h period have been previously described (15). The cell concentration was determined using a Coulter counter (Beckman Coulter, Miami, FL).…”
Section: Experimental and Theoretical Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…Fermentor culture conditions for CEN.PK113-7D oscillating with a 4 h period have been previously described (15). The cell concentration was determined using a Coulter counter (Beckman Coulter, Miami, FL).…”
Section: Experimental and Theoretical Proceduresmentioning
confidence: 99%
“…The periods of the transcriptional oscillations can be influenced by growth conditions, such as glucose availability, the amount of dissolved oxygen (DO) and by drug treatment (1014). Time resolved microarray data have demonstrated that the levels of certain transcripts correlate with each other during different phases of the cell cycle (3, 6, 15). Taken together, these studies support a possible correlation between gene transcription and metabolic function (16), as well as a link between transcriptional dynamics and energy requirements and energy release.…”
mentioning
confidence: 99%
See 3 more Smart Citations